2021
DOI: 10.3390/met12010050
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning Based Predictions of Fatigue Crack Growth Rate of Additively Manufactured Ti6Al4V

Abstract: The present work focusses on machine learning assisted predictions of the fatigue crack growth rate (FCGR) of Ti6Al4V (Ti64) processed through laser powder bed fusion (L-PBF) and post processing. Various machine learning techniques have provided a flexible approach for explaining the complex mathematical interrelationship among processing-structure-property of the materials. In the present work, four machine learning (ML) algorithms, such as K- Nearest Neighbor (KNN), Decision Trees (DT), Random Forests (RF), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In this work, the ML-based method was used to predict the fatigue life of AM titanium. However, it is important to acknowledge that other factors such as microstructure and various process parameters [36][37][38][39][40] can also potentially influence the fatigue life. To further enhance the accuracy and robustness of the prediction model, it is recommended that future research considers incorporating as many influencing variables as possible.…”
Section: Effects Of Svr Parameters On Predicted Results and Predictio...mentioning
confidence: 99%
“…In this work, the ML-based method was used to predict the fatigue life of AM titanium. However, it is important to acknowledge that other factors such as microstructure and various process parameters [36][37][38][39][40] can also potentially influence the fatigue life. To further enhance the accuracy and robustness of the prediction model, it is recommended that future research considers incorporating as many influencing variables as possible.…”
Section: Effects Of Svr Parameters On Predicted Results and Predictio...mentioning
confidence: 99%
“…Konda et al 164 used decision trees and extreme gradient boosting (XGB) algorithms to predict fatigue crack growth behavior of SLM Ti‐6Al‐4V under different post‐processing conditions. The results were compared by mean squared error (MSE) and coefficient of determination, which indicated that the XGB has better generalization ability on this problem.…”
Section: Ml‐based Methods For Fatigue Life Prediction Of Am Metalsmentioning
confidence: 99%
“…Single source [21][22][23][24]27,[30][31][32][34][35][36] Multi-source [16][17][18][19][20][28][29][30]33 the model, allowing the user to easily consider and implement confidence level bands in the stress life plots. 24 Nonetheless, in, 28 the mean and standard deviation of N f are estimated by using a PINN layout instead of a GPR, with a properly designed custom loss function that uses probability density function and cumulative distribution function with location parameter μ and scale parameter σ.…”
Section: Data Source Articlementioning
confidence: 99%
“…If the training database includes specimens coming from more experimental campaigns, where different thermal and surface post treatments were applied, their accountancy is recommended to assess their effect, either with a Boolean 17 or classification strategy. 20,24…”
Section: Article Techniquementioning
confidence: 99%
See 1 more Smart Citation